Diet and Lipid-Lowering Nutraceuticals in Pediatric Patients with Familial Hypercholesterolemia - Maria Elena Capra; Giacomo Biasucci; Giuseppe Banderali; Andrea Vania; Cristina Pederiva (MDPI AG, 2024)
Familial hypercholesterolemia is a genetically determined disease characterized by elevated plasma total and LDL cholesterol levels from the very first years of life, leading to early atherosclerosis. Nutritional intervention is the first-line treatment, complemented with nutraceuticals and drug therapy when necessary. Nutraceuticals with a lipid-lowering effect have been extensively studied in the past few decades, and have been recently included in international guidelines as a complement to nutritional and pharmacological treatment in subjects with dyslipidemia. In this review, we explore current nutritional interventions for dyslipidemia in childhood, with a specific focus on the main nutraceuticals studied for treating severe dyslipidemia in pediatric patients. Additionally, we briefly describe their primary mechanisms of action and highlight the advantages and risks associated with the use of lipid-lowering nutraceuticals in childhood.